E-commerce di Kalangan Mahasiswa Universitas Cokroaminoto Palopo dalam Membentuk Perilaku Budaya Konsumen - Ponglabba, Henry Ma’dika Ponglabba; Zainal, Zainal; Danial, Danial (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This research aims to find out and describe the reasons why PGSD students at Cokroaminoto Palopo University choose e-commerce as a place to shop, the shopping process, and the impact of online shopping on e-commerce. This research uses qualitative research methods with a virtual ethnographic approach. The technique for determining informants was carried out purposively. Data collection techniques were carried out through in-depth interviews, observation and documentation. Data analysis uses consumer culture theory by Celia Lury. The results of the research show that the reason why PGSD students at Cokroaminoto Palopo University choose e-commerce as a place to shop is because of several things, namely getting convenience and practicality when shopping, providing free shipping services, discount promos, more affordable prices, easy payment processes, getting goods that not available in Palopo City, and you don't have to leave the house to get the goods. The shopping process in e-commerce begins with paying attention to reviews related to the desired item, then selecting the item or shop, selecting the delivery option, selecting the payment option, and the final process of ordering the item. Shopping on e-commerce has positive and negative impacts on students. The positive impact is that it provides convenience and practicality for PGSD students at Cokroaminoto Palopo University, while the negative impact is that it forms continuous shopping behavior and gives birth to sign consumption behavior (non-utilitarian) or shopping not because of need but because of desire.